Documentation and ethnobotanical survey of wild edible plants from Kolhapur district - D, Jadhav V; D, Mahadkar S; R, Valvi S (Recent Research in Science and Technology, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The present study deals with the identification, documentation and ethno-botanical exploration with respect to food value of wild edible plants from Kolhapur district. Total 50 wild edible plants were surveyed. Edible parts of wild plants (fruit, flower, leaves, tubers and inflorescences) are the nature’s gift to mankind; these are not only delicious and refreshing but also the chief source of vitamin, minerals and protein. The wild edible plants are the normal food of cattle grazers and the forest tribes. Although the popularity of these wild forms of fruits, flowers and tubers has declined, it is considered that special attention should be paid to them in order to maintain and improve this important source of food supply.